2017
DOI: 10.1590/2359-3997000000197
|View full text |Cite
|
Sign up to set email alerts
|

Impact of free thyroxine levels and other clinical factors on bare metal stent restenosis

Abstract: Objective: Thyroid hormones have both direct and indirect effects on thermogenesis such as modulating vascular smooth muscle cell proliferation. However, the influence of more subtle changes in thyroid hormones on coronary atherosclerosis remains a matter of speculation. Smooth muscle cells play a crucial role in the pathogenesis of in-stent restenosis (ISR). However, the relationship between free thyroxine (fT4) and ISR has not been studied. In the present study, we aimed to assess the role of preprocedural s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…To this effect, computed tomography angiography findings of patients with overt and subclinical hyperthyroidism had revealed a greater extent of high-grade and overall coronary stenoses, plaque burden, and high-risk plaque hallmarks than the euthyroid patients [12]. The data from Canpolat et al substantiate this point, whereby the preprocedural serum level of fT4 was found to be a significant independent factor of ISR in patients with successful BMS implants [13].…”
Section: Discussionmentioning
confidence: 95%
“…To this effect, computed tomography angiography findings of patients with overt and subclinical hyperthyroidism had revealed a greater extent of high-grade and overall coronary stenoses, plaque burden, and high-risk plaque hallmarks than the euthyroid patients [12]. The data from Canpolat et al substantiate this point, whereby the preprocedural serum level of fT4 was found to be a significant independent factor of ISR in patients with successful BMS implants [13].…”
Section: Discussionmentioning
confidence: 95%
“…Only Canpolat et al found that high preoperative serum FT4 level was an effective independent predictor of BMS restenosis in patients with stable and unstable angina pectoris. They suggested that serum FT4 increases the risk of ISR by enhancing the activity of the renin-angiotensin system and the proliferation of vascular smooth muscle cells ( 38 ). Therefore, this study is the first to identify thyroxine as a significant predictor of ISR after drug-eluting stent implantation.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a number of studies have found a correlation between thyroid hormone and acute coronary syndrome (ACS), and low FT3 is an independent risk factor for coronary artery severity and MACE after PCI [ 17 , 18 , 19 , 20 , 21 , 22 ]. Studies have also explored the relationship between thyroxine and ISR [ 23 ]. Canpolat et al .…”
Section: Discussionmentioning
confidence: 99%
“…Canpolat et al . [ 23 ] reported that elevated plasma FT4 levels were an independent risk factor for ISR after BMS implantation, but few studies have investigated the relationship between FT3 and ISR. In this study, it was found that low FT3 was an independent risk factor for myocardial infarction, recurrent ISR, and TVR in patients with ISR after revascularization, and its mechanism may involve the following aspects.…”
Section: Discussionmentioning
confidence: 99%